2005
DOI: 10.1186/bcr1027
|View full text |Cite
|
Sign up to set email alerts
|

CYP17 5'-UTR MspA1 polymorphism and the risk of premenopausal breast cancer in a German population-based case–control study

Abstract: Introduction Studies on the association between the cytochrome P450c17α gene (CYP17) 5'-untranslated region MspA1 genetic polymorphism and breast cancer risk have yielded inconsistent results. Higher levels of estrogen have been reported among young nulliparous women with the A2 allele. Therefore we assessed the impact of CYP17 genotypes on the risk of premenopausal breast cancer, with emphasis on parity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 27 publications
4
20
2
Order By: Relevance
“…In accordance with our results, Verla-Tebit et al (2005) found no evidence of the previously reported (Feigelson et al 1997;Ambrosone et al 2003) effect modification for later age at menarche by the CYP 17 TT (A1/A1) genotype. Verla-Tebit et al (2005) observed an increased risk for oral contraceptive users compared with nonusers among nulliparous women with the TT (A1/A1) genotype.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In accordance with our results, Verla-Tebit et al (2005) found no evidence of the previously reported (Feigelson et al 1997;Ambrosone et al 2003) effect modification for later age at menarche by the CYP 17 TT (A1/A1) genotype. Verla-Tebit et al (2005) observed an increased risk for oral contraceptive users compared with nonusers among nulliparous women with the TT (A1/A1) genotype.…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings were reported by Verla-Tebit et al (2005). It was reported that early pregnancy has a protective role against breast cancer; women whose FFTP occur after the age of 30 have a two to fivefold increase in breast cancer risk compared with women having a FFTP before age of 20.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations